3D Printing for Kiswah Adornment: An Applied Investigation into Additive Manufacturing as an Alternative to Gold Thread Embroidery - Madani, Rafat Saleh (Journal of Posthumanism, 2026)
The Kiswah, the embroidered black silk covering of the Holy Kaaba in Makkah, is the most prestigious work of Islamic textile craftsmanship and is renewed annually at substantial cost. The traditional gold and silver thread embroidery is vulnerable to ultraviolet, thermal, and hydric degradation, and the artisanal labour pool required to execute it is contracting. This applied study investigates the technical feasibility of substituting selected components of the gold thread ornamentation with three-dimensionally printed elements. Three candidate material systems were evaluated: gold-look polylactic acid (PLA) processed by fused deposition modelling, ultraviolet-stabilised photopolymer resin loaded with metallic pigment processed by stereolithography (SLA), and metal-loaded glycol-modified polyethylene terephthalate (PETG-Cu). Eight specimens per material - comprising 24 printed test pieces and four traditional embroidered control specimens - were subjected to a 12-month exposure protocol on an outdoor test rig in Makkah, with periodic instrumented assessment of colour change (delta E), gloss retention, adhesion to the silk substrate, and dimensional stability. Results demonstrate that all three printed material systems exhibited measurable degradation, but that UV-stabilised SLA resin and PETG-Cu both retained colour and adhesion sufficient to be considered candidate substitutes for non-contact ornamental elements. Gold-look PLA failed thermal stability criteria within the first three summer months. None of the printed systems matched the directional metallic sheen of traditional couched zari thread. The study concludes that AM is technically feasible for selected ornamental components but, in its current state, is best deployed in a hybrid workflow alongside traditional embroidery rather than as a full substitute.